CAPABILITY OF DIFFERENT BREEDS OF DONOR CATTLE TO PRODUCE EMBRYOS AT THE CIPELANG LIVESTOCK EMBRYO CENTER, BOGOR, WEST JAVA - Crista Damaris; Anny Rosmayanti; Siti Darojah; Nurul Isnaini (Universitas Syiah Kuala, 2023)
The objective of this research was to investigate the capability of the donor cattle to produce embryos by comparing three cattle breeds, namely Bos taurus beef cattle (Limousin), Bos taurus dairy cattle (Friesian Holstein/FH), and Bos indicus beef cattle (Peranakan Ongole/PO). This research was observational method with in vivo embryo production method and a nonsurgical embryo collection method (flushing). The data collected were then processed using the one way ANOVA method. The results showed that the number of CL, response rate, total number of embryos, and recovery rate in PO cattle, FH cattle, and Limousin cattle did not differ significantly (P0.05). The appropriate number of embryos to be transferred and degenerative embryo were significantly different among PO cattle, FH cattle, and Limousin cattle (P0.05), while the unfertil ova, fertilization rate, and transferable embryo did not differ among cattle breed (P0.05). This research concluded that each breed of the donor cattle produced embryos with varies quality and the best quality of embryo production is found in Limousin cattle.